Determinan Audit Report Lag Dengan Efektivitas Komite Audit Sebagai Variabel Pemoderasi (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020) - Kartikasari Kartikasari; Siti Mutmainah (Diponegoro Journal of Accounting, 2022)
This study aims to analyze the determinants of audit report lag models. The dependent variable used in this study is audit report lag, while the independent variables are company size, profitability, auditor reputation. This study also uses a moderating variable, namely the audit committee’s effectiveness, as a proxy for the number of audit committee meetings in one year. The population in this study were all companies listed on the Indonesia Stock Exchange in 2016-2020. A purposive sampling method was used to determine the research sample. The sample used is as many as 88 companies in 2016-2020, so the total sampel used is 440 samples. The statistical technique used in this research is panel data with multiple regression analysis method with Partial Least Square (PLS) moderating effect SmartPLS 3.0 software.The results of this study indicate that the profitability and effectiveness of the audit committee have a negative and significant effect on audit report lag. In contrast, company size and auditor reputation have no significant effect on audit report lag. The results also show that the effectiveness of audit committee has no moderating effect.